Answer:
10f-30g
Step-by-step explanation:
we have:
5(2f - 6g)
we apply distributive property:
5(2f - 6g)
5*2f+5*(-6g)
finally we have:
10f-30g
Answer:
Step-by-step explanation:
6x - 2y = -4
y= 3x + 2
We see that y = 3x + 2 so we can use that value of Y everytime we see i in the other equation.
6x - 2(3x +2) = -4
Now usually we'd we simply solve for X.
6x - 6x -4 = -4
This clearly does not work as we cannot get rid of X
Therefore, this system of equations has no solution we can find through substitution
Answer:
c. 50kg = 50,000g
Step-by-step explanation:
We have to solve these following rule of three to see which of the following is a correct conversion of 50kg.
a)
Each kg has 1000g
So
1kg - 1000g
50kg - xg
x = 50*1000
x = 50,000g
Conversion a) is wrong
b)
Each kg has 1000000mg
So
1kg - 1000000g
50kg - x mg
x = 50*1000000
x = 50,000,000 mg
Conversion b) is wrong
c)
In a), we have already converted 50kg to g. We have verified that 50kg = 50,000g. So c. is correct
d)
In b), we have already converrted 50kg to mg. We have verified that 50kg = 50,000,000g. So d. is wrong
Step-by-step explanation:
4x+2=8+6x
-2x=6
x=-3
Hope it helps
Answer:
1.5
Step-by-step explanation:
-3/8=-0.375
-1/4=-0.25
the negatives cancel each other out so it is 0.375/0.25
.25 goes into .375 1.5 times, so the answer is 1.5
Have a good day!